Pendampingan Khotmil Qur'an Dalam Mewujudkan Masyarakat Gemar Membaca Al-Qur'an - Muhammad Yasin; Eka Widyanti; Iswanto Iswanto (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
The book of Muslims is the Koran. Allah sent down the revelation of the Qur'an through the angel Gabriel to the Prophet Muhammad sallallaahu 'alaihi wa sallam, a miracle received by the Prophet Muhammad sallallaahu 'alaihi wa sallam a very special book and also as a guide (Al-huda) for people who believe. the focus of dedication in this mentoring is to carry out the Miftahul Ulum Mushola Management Assistance activities as an effort to optimize the Musholla's function as a place to learn to recite the Al-Qur'an and as a place for five daily prayers. This service uses the Participatory Action Research method where the writer is actively involved in direct service activities both as a Koran teacher and as a community member of the Musholla environment. In the Participatory Action Research method there are three pillars in its application, namely: research methodology, action, and participation. Service activities related to Musholla Assistance can strengthen friendship ties and can grow our generation. because the Qur'an is a guide to daily life. Therefore, it is not enough for us to read it until it is finished but do not understand its contents.